Amphibian parasites of the Order Dermocystida (Ichthyosporea): current knowledge, taxonomic review and new records from Brazil - Borteiro, Claudio; Baldo, Diego; Maronna, Maximiliano M.; Baêta, Délio; Sabbag, Ariadne Fares; Kolenc, Francisco; Debat, Claudio Martínez; Haddad, Célio F. B.; Cruz, Juan Carlos; Verdes, José Manuel; Ubilla, Martín (Zootaxa, 2018)
Amphibian parasites of the Order Dermocystida (Ichthyosporea) are widespread pathogens known mainly from Europe and North America, which cause primarily a disease of skin and subcutaneous tissue in their hosts. The taxonomy of these organisms has been problematic given their conserved morphology, similar clinical disease and pathology. Currently recognized taxa belong to the three closely related genera, Amphibiocystidium, Amphibiothecum, and Rhinosporidium, whereas species of Dermocystidium and Sphaerothecum destruens include fish parasites. Here, we review the taxonomy of Dermocystida based on a molecular phylogenetic analysis, principally of amphibian parasites, including DNA sequences obtained from amphibian hosts collected in the central-eastern region of South America. A new taxonomic arrangement is proposed, which includes the designation of type material for Dermocystidium pusula, synonymization of Amphibiothecum with Dermocystidium, and the restriction of Amphibiocystidium to its type species A. ranae. We also review the taxonomic status of Dermosporidium hylarum until the present work included in the synonymy of the human and animal pathogen R. seeberi, and considered herein as a valid taxon, however. In addition, a new species of Sphaerothecum parasitic to amphibians is described, being the first record of this genus in the southern hemisphere and in an amphibian host.